Oleoylethanolamide Protects Against Acute Liver Injury by Regulating Nrf-2/HO-1 and NLRP3 Pathways in Mice - Hu, Jiaji; Zhu, Zhoujie; Ying, Hanglu; Yao, Jie; Ma, Huabin; Li, Long; Zhao, Yufen (Frontiers in Pharmacology, 2021)
Acute liver injury is a rapidly deteriorating clinical condition with markedly high morbidity and mortality. Oleoylethanolamide (OEA) is an endogenous lipid messenger with multiple bioactivities, and has therapeutic effects on various liver diseases. However, effects of OEA on acute liver injury remains unknown. In this study, effects and mechanisms of OEA in lipopolysaccharide (LPS)/D-galactosamine(D-Gal)-induced acute liver injury in mice were investigated. We found that OEA treatment significantly attenuated LPS/D-Gal-induced hepatocytes damage, reduced liver index (liver weight/body weight), decreased plasma alanine aminotransferase (ALT), aspartate aminotransferase (AST) and lactate dehydrogenase (LDH) levels. Moreover, mechanism study suggested that OEA pretreatment significantly reduced hepatic MDA levels, increased Superoxide Dismutase (SOD) and Glutathione Peroxidase (GSH-PX) activities via up-regulate Nrf-2 and HO-1 expression to exert anti-oxidation activity. Additionally, OEA markedly reduced the expression levels of Bax, Bcl-2 and cleaved caspase-3 to suppress hepatocyte apoptosis. Meanwhile, OEA remarkedly reduced the number of activated intrahepatic macrophages, and alleviated the mRNA expression of pro-inflammatory factors, including TNF-α, IL-6, MCP1 and RANTES. Furthermore, OEA obviously reduced the expression of IL-1β in liver and plasma through inhibit protein levels of NLRP3 and caspase-1, which indicated that OEA could suppress NLRP3 inflammasome pathway. We further determined the protein expression of PPAR-α in liver and found that OEA significantly increase hepatic PPAR-α expression. In addition, HO-1 inhibitor ZnPP blocked the therapeutic effects of OEA on LPS/D-Gal-induced liver damage and oxidative stress, suggesting crucial role of Nrf-2/HO-1 pathway in the protective effects of OEA in acute liver injury. Together, these findings demonstrated that OEA protect against the LPS/D-Gal-induced acute liver injury in mice through the inhibition of apoptosis, oxidative stress and inflammation, and its mechanisms might be associated with the Nrf-2/HO-1 and NLRP3 inflammasome signaling pathways.